2021
DOI: 10.31933/dijms.v3i1.977
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and the Firm's Value

Abstract: The cause of this research is to investigate and prove the impact of ROA, ROE, NPM, and GPM on firm’s value (Tobin's Q) either partially or simultaneously and decide which profitability ratio is more dominant in explaining Tobin's Q variance. The analysis was carried out on companies listed in the Jakarta Islamic Index (JII) for 2015-2020. The sample selected was issuers consistently registered with JII during the 2015-2020 period, and 11 issuers were selected. The results of the analysis show ROA and NPM part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…This situation will be used by company managers to obtain capital resources in the form of shares. The results of this study are not in line with research conducted Jonnius & Setya Marsudi (2021) which is able to prove that Profitability individually has a significant positive effect on firm value, and the hypothesis is accepted. The positive effect of firm value is a good prospect for companies to attract investors, because Profitability is the most important indicator for a company, where the higher the ratio, the higher the profit the company has.…”
Section: Discussioncontrasting
confidence: 95%
“…This situation will be used by company managers to obtain capital resources in the form of shares. The results of this study are not in line with research conducted Jonnius & Setya Marsudi (2021) which is able to prove that Profitability individually has a significant positive effect on firm value, and the hypothesis is accepted. The positive effect of firm value is a good prospect for companies to attract investors, because Profitability is the most important indicator for a company, where the higher the ratio, the higher the profit the company has.…”
Section: Discussioncontrasting
confidence: 95%
“…The implications of studying the financial performance of the Indian oil exploration and drilling sector are profound and far-reaching, with implications extending across various dimensions of the economy and society [22][23][24][25][26][27]. Understanding the sector's financial dynamics can provide policymakers with valuable insights to formulate effective regulations and policies that foster investment, innovation, and sustainable development.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…Research has consistently shown a positive and significant effect of profitability, measured by Return on Assets (ROA), on firm value, indicated by Tobin's Q (Hill & Jones, 1992;Jonnius & Marsudi, 2021;Kurniati et al, 2022;Sutrisno & Panuntun, 2020). However, Return on Equity (ROE) has been found to either negatively impact or have no significant effect on Tobin's Q (Jonnius & Marsudi, 2021;Siti Fatimah, 2022;Nguyen et al, 2022).The role of dividend policy in mediating the relationship between profitability and firm value has also been explored.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Research has consistently shown a positive and significant effect of profitability, measured by Return on Assets (ROA), on firm value, indicated by Tobin's Q (Hill & Jones, 1992;Jonnius & Marsudi, 2021;Kurniati et al, 2022;Sutrisno & Panuntun, 2020). However, Return on Equity (ROE) has been found to either negatively impact or have no significant effect on Tobin's Q (Jonnius & Marsudi, 2021;Siti Fatimah, 2022;Nguyen et al, 2022).The role of dividend policy in mediating the relationship between profitability and firm value has also been explored. Studies like Dewi and Abundanti (2020) and Astuti and Yadnya (2019) found significant mediation by dividend policy in the Indonesia Stock Exchange, whereas Fitriani et al (2017) and Mahirun et al (2023) found no significant mediation effect, highlighting that this relationship can vary by period and geography.…”
Section: Empirical Reviewmentioning
confidence: 99%